Rancang Bangun “Asitorik” sebagai Media Pembelajaran Praktek Mahasiswa Akuntansi - Asmoro, Wiwiek Kusumaning; Izzah, Abidatul (Politeknik Ganesha Medan, 2018)
Learning about ”Public Sector Accounting” is require skills in credit debit transaction theory, recording a ledger, to compiling reports. However, students and lecturers have difficulty in terms of time effectiveness in understanding concepts and evaluating assessments. Thus it takes an e-learning that can help students in understanding the flow of making Public Sector Accounting reports completely. Therefore in this study an accrual-based Public Sector Accounting Application was made in an effort to improve the ease of learning practice of accounting students. This app is built based on the web using the PHP programming language and mySQL database. Firstly, needs analysis has been conducted based on the learning process of Public Sector Accounting Practicum in Accounting Department of Politeknik Kediri. Then, the app has been successfully built and tested so students so that it can manipulate an account, journal, and transaction automatically. Finally, it also prints Ledger, Budget Realization Report, Report on Changes in Budget Balance, Balance Sheet, Operational Report, and Statement of Changes in Equity.